2021
DOI: 10.1016/j.bja.2021.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative inflammatory mediators and postoperative delirium: systematic review and meta-analysis

Abstract: Background: Postoperative delirium has eluded attempts to define its complex aetiology and describe specific risk factors. The role of neuroinflammation as a risk factor, determined by measuring blood levels of preoperative 'innate' inflammatory mediator levels, has been investigated. However, results have been conflicting. We conducted a systematic review and meta-analysis of the evidence on associations between preoperative blood levels of inflammatory mediators and postoperative delirium in the older person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 42 publications
(137 reference statements)
7
45
1
Order By: Relevance
“…62 Indeed, a recent meta-analysis showed that higher levels of IL-6 are associated with postoperative delirium. 69 Interestingly, we observe lower levels of lymphocytes in older patients in the preoperative period, consistent with previous studies investigating changes in key immune cell populations, and support the development of immunosenescence with increasing age. 70 There is also evidence of changes in the distribution of lymphocyte subtypes in older individuals, and cytokines such as IL-6 are known to affect the differentiation of lymphocyte subpopulations.…”
Section: Discussionsupporting
confidence: 91%
“…62 Indeed, a recent meta-analysis showed that higher levels of IL-6 are associated with postoperative delirium. 69 Interestingly, we observe lower levels of lymphocytes in older patients in the preoperative period, consistent with previous studies investigating changes in key immune cell populations, and support the development of immunosenescence with increasing age. 70 There is also evidence of changes in the distribution of lymphocyte subtypes in older individuals, and cytokines such as IL-6 are known to affect the differentiation of lymphocyte subpopulations.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports indicate that delirium is associated with increases in immune-inflammatory biomarkers, including interleukin (IL)-1, IL-6, soluble tumor necrosis factor (TNF) receptor, and other cytokines [ 7 , 8 ]. Additionally, meta-analyses have reported that POD is correlated with the concentrations of peripheral and cerebrospinal fluid (CSF) inflammatory markers, including C-reactive protein (CRP), IL-6, -8, and -10, and TNF-α [ 9 , 10 ]. These studies showed that certain inflammatory markers are associated with POD.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that peripheral inflammatory markers, such as the NLR and PLR, are associated with the development of POD after hip surgery, cardiac surgery, and esophagectomy [ 15 , 16 , 17 , 18 ]. Other studies have reported that the association between the preoperative blood levels of inflammatory mediators and POD may be affected by the type of surgery [ 9 , 10 ]. The special circumstances associated with certain types of surgery may contribute to the etiology of POD.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that systemic and neuroinflammation play a key role in the development of delirium [ 7 10 ]. Many human studies have investigated inflammatory cytokines in delirium subjects [ 11 , 12 ]. Although a meta-analysis showed increased levels of IL-6 in blood from POD patients, the evidence for other inflammatory markers is still unclear [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many human studies have investigated inflammatory cytokines in delirium subjects [ 11 , 12 ]. Although a meta-analysis showed increased levels of IL-6 in blood from POD patients, the evidence for other inflammatory markers is still unclear [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%